Transformasi Tari Bungkus di Kabupaten Simeulue - Putri Khairani (Gesture: Jurnal Seni Tari, 2016)
The research discuss about transformation of bungkus dance in Simelue Regency. The Bungkus dance is one of traditional dance in the Simelue Regency that comes from Sibolga Costal region. The Purpose of the research is to understand the history and transformation bungkus dance in Simelue Regency.In the research discussion, used consist of three Sumaryono and Acculturation theory by Koentjaraningrat. The method that used in this research discussion is Qualitative Descriptive method. The time research of Bungkus Dance transformation has done two month since september untuk october 2015. The population of research is all of Simeulue Society and the sample of this ersearch is the lkeader of tradition, informan, artists and general society who know about bungkus dance. Based on the research that has done know that the transformation  bungkus dance can be seen from style, feel, and sense.